Response of Salvinia cucullata to high NH(4)(+) concentrations at laboratory scales - Jampeetong A. (2014)
Growth, morphology, NH(4)(+) uptake and mineral allocation in Salvinia cucullata Roxb. ex Bory grown with different amounts of NH(4)(+) were investigated. Plants of uniform size were grown on full strength Smart and Barko medium with different NH(4)(+) concentrations (0.5, 1, 5, 10 and 15mM) and incubated in a greenhouse for four weeks. Salvinia cucullata grew well in the medium with 0.5-1mM NH(4)(+) with a relative growth rate of 0.11-0.12d(-1) without exhibiting NH(4)(+) toxicity symptoms. With an NH(4)(+) concentration above 5mM, plant growth was suppressed and signs of NH(4)(+) toxicity were observed. NH(4)(+) toxicity symptoms were obvious in plants supplied with 10mM and 15mM NH(4)(+). These plants had low growth rates, short roots, low numbers of roots and showed chlorosis. Rotted roots and stems were also found in plants fed with 15mM NH(4)(+). This species had a high uptake rate even though the NH(4)(+) concentrations increased, making it an ideal candidate for growth in eutrophic environments. The high NH(4)(+) concentration had a negative effect on K uptake resulting in low K concentration in the plant tissue, but the plants increased N content in plant tissue. Thus, harvested plants can be used as soil fertilizer or for animal feed. Furthermore, maintaining plant biomass can improve the efficiency of water treatment.